Reappraising the Reincarnation Debate in an African Culture: A Conceptual Clarification - Akinpelu A. Oyekunle; Ezekiel S.N. Mkhwanazi (E-Journal of Humanities, Arts and Social Sciences, 2024)
This paper re-examines the reincarnation debate within the African cultural context, with a focus on the Yoruba people of southwestern Nigeria and the Nguni people of Southern Africa. The reincarnation debate has generated the query that the term/concept ‘reincarnation’ does not describe or capture African socio-cultural thinking and belief about the interrelationship between the living and the dead. Alternative terms that align with African intellectual heritage and cultural practices have emerged because of this query, while critiques have been advanced against the alternative terms’ arguments. Thus, the reappraisal of the reincarnation debate becomes necessary to provide analytical justification for the proposed alternative terms for the phenomenon of reincarnation within the African socio-cultural ecosystem. Adopting an expository and analytic method of philosophising, this paper calls for a conceptual clarification of what reincarnation could mean in the African context. This paper argued that the phenomenon of reincarnation explains one of the ways Africans promote family solidarity and unbroken inter-generational unity in the cycle of existence. As such, the African conception of reincarnation encapsulates a philosophical explanation of the perpetuation of the family of the past on a cyclic continuum involving present and future generations. The study concludes by emphasising the importance of reconceptualising reincarnation within the African conceptual framework to ensure the logical and intelligible representation of African intellectual heritage and identity, particularly considering the global epistemicide of local knowledge systems.